2020
DOI: 10.1088/2053-1591/ab6c99
|View full text |Cite
|
Sign up to set email alerts
|

Stainless steel coated with carbon nanofiber/PDMS composite as anodes in microbial fuel cells

Abstract: Modification of electrode surfaces is a promising strategy to improve microbial fuel cell (MFC) performance. Here we report a new functionalization process to improve interfacial electron transfer, biocompatibility and corrosion resistance of stainless steel (SS) electrodes used as anodes in MFCs. SS anodes prepared by surface modification with a thin layer (200 μm) of conducting composite made of polydimethylsiloxane (PDMS) doped with commercially available carbon nanofibers (CNF), are described. Electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
(33 reference statements)
0
14
1
Order By: Relevance
“…Indeed, the authors justified this poor electrical performance by the low conductivity of the polyaniline and the compact passivated layer (oxide layer) formed between the polymer-Cu surfaces. Compared with the performance of MFCs with other anode materials using wastewater as inoculum, the power density of 500 µm-thick CNF-PDMS coated Cu anodes was higher than what we previously reported for stainless steel anodes coated with CNF-PDMS (19 mW m −2 ) [19] and bare carbon clothe (50 mW m −2 ) [1]. However, the power density was lower than those obtained with carbon felt (100 mW m −2 ) [29] and carbon paper (104 mW m −2 ) [28] anodes, as previously described.…”
Section: Electricity Production Performancecontrasting
confidence: 69%
See 2 more Smart Citations
“…Indeed, the authors justified this poor electrical performance by the low conductivity of the polyaniline and the compact passivated layer (oxide layer) formed between the polymer-Cu surfaces. Compared with the performance of MFCs with other anode materials using wastewater as inoculum, the power density of 500 µm-thick CNF-PDMS coated Cu anodes was higher than what we previously reported for stainless steel anodes coated with CNF-PDMS (19 mW m −2 ) [19] and bare carbon clothe (50 mW m −2 ) [1]. However, the power density was lower than those obtained with carbon felt (100 mW m −2 ) [29] and carbon paper (104 mW m −2 ) [28] anodes, as previously described.…”
Section: Electricity Production Performancecontrasting
confidence: 69%
“…In this study, Cu anode surfaces were modified with thin layer of low-cost and mechanical stable CNF-PDMS (Polydimethylsiloxane) coating (Figure 1). PDMS is an attractive polymer with physically and chemically stable properties [19]. Recently, we demonstrated that PDMS doped with CNF is a conducting polymer providing more significant electrical active sites for electron transfer between exoelectrogenic bacteria and stainless steel coated electrodes [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both configurations offer better degradation performances than classical Fenton and conventional ZVI-based Fenton. Moreover, electrical energy performances of the GF process obtained with both the GF-A and GF-B configuration are higher than electrical performances of microbial fuel cell technology, another electrochemical technology using bacteria to produce electrical energy from biodegradable organic molecules in wastewater with maximum power comprised between 1 mW·m −2 and 1 W·m −2 [ 33 , 34 ]. The electrical energy generated by the GF process can be harvested and exploited using an external circuit based on electronic power converters and digital processing devices that extract the maximum amount of electrical power and increase the voltage as needed.…”
Section: Resultsmentioning
confidence: 99%
“…Coating a layer of polymers on carbon matrix can improve the bacteria-electrode interaction, electrical conductivity, corrosion resistance and hydrophilicity, leading to a strong adhesion of microbes, extracellular electron transfer and operation stability. [247][248][249] For example, when poly(3-aminophenylboronic acid) (p-PAPBA) was coated on carbon cloth (CC) anode, the electron transport was promoted due to the chemical interaction between the cell surface and p-PAPBA film. [248] Similarly, owing to the positive charge and hydrophilicity of the ionic liquid polymer and polydiallyldimethylammonium chloride (PDDA), the electrostatic interaction with CC or carbon felt (CF) benefited the electron transfer.…”
Section: Polymer-based Carbon Composite Anodementioning
confidence: 99%